2019
DOI: 10.2478/s11756-019-00191-5
|View full text |Cite
|
Sign up to set email alerts
|

What factors influence colonization of lichens, liverworts, mosses and vascular plants on snags?

Abstract: The dead standing trees i.e. snags are known as habitat for epiphytic and epixylic species including first of all lichens and bryophytes. The vascular plants are much rarer on this type of coarse woody debris (CWD). The eighty snags (CWD elements higher than 1.5 m) of Norway spruce Picea abies and beech Fagus sylvatica in the Karkonosze Mts. were examined for the presence of lichens, liverworts, mosses and vascular plants. The height of snags, their decomposition stage, cover of bark, diameter at breast height… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 36 publications
2
8
0
Order By: Relevance
“…Sfenthourakis and Triantis () also found that small islands had a lower specialist‐to‐generalist ratio than large islands and that the ratio linearly increased with island area. Liverworts are more likely than mosses to be specialists (Staniaszek‐Kik, Chmura, & Żarnowiec, ), and our results were consistent with these findings.…”
Section: Discussionsupporting
confidence: 89%
“…Sfenthourakis and Triantis () also found that small islands had a lower specialist‐to‐generalist ratio than large islands and that the ratio linearly increased with island area. Liverworts are more likely than mosses to be specialists (Staniaszek‐Kik, Chmura, & Żarnowiec, ), and our results were consistent with these findings.…”
Section: Discussionsupporting
confidence: 89%
“…Therefore, despite the complex nature of our results, they indicate that it is easier to find variables describing forest characteristics that predicts richness of macrofungi and lichens (12 and nine, respectively) than vascular plants and bryophytes (five and seven, respectively). This can be illustrated by a much higher proportion of macrofungal and lichen specialist species, compared to vascular plants and bryophytes (Nordén et al 2013;Staniaszek-Kik et al 2019). This was also true for the spruce and pine forest types (14 and nine forest characteristic variables, respectively), but not to the same extent for the mixed tree species types (five for deciduousconiferous mixed and seven for coniferous-mixed forests).…”
Section: Discussionmentioning
confidence: 93%
“…Standing wood in the Giant Mountains (Czech Republic) is an important habitat colonised mostly by lichens. Species diversity in this group is strongly linked to vegetation type and the occurrence of snags, the distribution of which is related to forest management introduced after dieback of spruce caused by pollution in the 1980s (Staniaszek-Kik et al 2019). A relationship between vegetation type and lichen distribution and diversity was also found by Vondrák and Kubásek (2019).…”
Section: Main Problems Discussed In the Presented Studiesmentioning
confidence: 94%
“…The abundance of standing deadwood and logs in different stages of decay is dependent on many factors. Natural and anthropogenic factors that influence the diversity of bryophytes and lichens found on deadwood and other organic substrates are discussed in the Special Issue (Staniaszek-Kik et al 2019;Vondrák and Kubásek 2019). Standing wood in the Giant Mountains (Czech Republic) is an important habitat colonised mostly by lichens.…”
Section: Main Problems Discussed In the Presented Studiesmentioning
confidence: 99%